Ciencia e investigación agraria 2018
DOI: 10.7764/rcia.v45i2.1865
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of paper mill pelletized waste using germination and biomass production as bioindicators

Abstract: P. Undurraga, J. Hirzel, J. Celis, C. Pérez, and M.A. Sandoval. 2018. Toxicity of paper mill pelletized waste using germination and biomass production as bioindicators. Cien. Inv. Agr. 45(2): 147-157. The use of wood residues to produce energy and steam in the pulp and paper industry generates ash waste and sewage sludge that contain nutrients for plants as a potential fertilizer. The objective of this study was to evaluate the possible toxic effects of pelletized waste from the pulp and paper industry using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This observation suggests that PMS contains organic matter and essential nutrients that can enrich the soil. Undurraga et al reported no acute or subacute toxic effects on seed germination when PMS prepared as pellets was applied to soil [36]. In particular, there is also a concern about contamination from toxic substances in wastewater, as PMS is a solid waste generated in the wastewater treatment process.…”
Section: Germination Index (Gi)mentioning
confidence: 99%
“…This observation suggests that PMS contains organic matter and essential nutrients that can enrich the soil. Undurraga et al reported no acute or subacute toxic effects on seed germination when PMS prepared as pellets was applied to soil [36]. In particular, there is also a concern about contamination from toxic substances in wastewater, as PMS is a solid waste generated in the wastewater treatment process.…”
Section: Germination Index (Gi)mentioning
confidence: 99%
“…In some countries, those materials are characterized by their high Na content and electrical conductivity, which may affect the plants production. However, studies made in Chile indicated that the use of by-products from the cellulose industry didn't affect the germination and growth of radish (Raphanus sativus L.) in Alfisol soil (Undurraga et al, 2018). In Chile, the mains cellulose industry wastes are located in the south-central and south, which is coincident with the main area planted with forest.…”
Section: Introductionmentioning
confidence: 99%